Implementasi Ekonomi Syariah bagi Pemberdayaan Ekonomi Pondok Pesantren Darul Ulum As’adiyah Tokare - Muthia Huzaemah (Universitas Veteran Bangun Nusantara, 2024)
The essence of this research is to provide an understanding of the implementation of Islamic economics for the economic empowerment of Darul Ulum As'adiyah Tokare Islamic Boarding School. In the face of pesantren economic empowerment, every pesantren generally has several kinds of assets, such as facilities, buildings, buildings, plantations, entrepreneurship, and other assets that can be used for operational purposes or madrasah needs. Various existing potentials have not been able to be explored by the boarding school, so that the boarding school still has dependence on funds and funding sources both from donors, community leaders around the boarding school thanks to support and support for the development of the boarding school. For this reason, the community service team from the Department of Sharia Economics -STAI Al-Gazali Soppeng was present to conduct socialization through the implementation of Islamic economics for the economic empowerment of Islamic boarding schools for Darul Ulum As'adiyah Tokare Islamic Boarding School. The socialization material presented to the boarding school residents is the result of previous studies in the form of research, manuscripts that have been published in journals, books and trusted websites. As a result of this activity, the team successfully completed the service at Darul Ulum As'adiyah Tokare Islamic Boarding School. Various potentials owned by the boarding school such as waqf buildings, waqf land, building assets, sports facilities, land and human resources can be developed into a source of economic empowerment managed based on the s economy.